Divergence and Convergence of Royalty Determinations between Compulsory Licensing under the TRIPS Agreement and Ongoing Royalties as an Equitable Remedy. Issue 1 (March 2020) - Shore, David
Patent rights are recognized as a property asset with an attendant right to exclude. However, recent policy developments highlight that the right to exclude is not inviolable. This paper explores two rapidly evolving exceptions to patent exclusivity, both of which take the form of compulsory licenses. First, under the international Agreement on Trade-Related Aspects of Intellectual Property Rights ("TRIPS"), national governments can compel patent owners to out-license technology in service of greater good. These egalitarian compulsory licenses improve access to technology but undermine patent value. Second, compulsory licenses are increasingly relied upon as an equitable remedy in U.S. patent litigation. Typically referred to as "ongoing royalties, " these court-mandated compulsory licenses are a modern alternative to injunctions against adjudged infringers. TRIPS compulsory licenses and ongoing royalties arise under independent legal frameworks, but necessarily invoke parallel economic considerations. While the wisdom of each has been discussed at length by others, this paper explores principles of royalty determination employed in each context. Considering both frameworks, an analysis of where each succeeds and fails is provided, together with an exploration of optimized royalty frameworks.